Historian jalili jalil and his role in preserving the kurdish heritage - Khudher, Haji; Al-Jawadi, Ghassan (Humanities Journal of University of Zakho, 2022)
Abstract: The Soviet Kurdish historian and researcher Jalili Jalil is one of the prominent Kurdish historians in our Kurdish contemporary history. He comes from an educated family that has a role in folklore and history of the Kurds beyond the Caucasus from those who devoted their lives to serving culture through his interest in Kurdish history and folklore, However, he worked in this field for more than fifty years and still, he has been interested in various aspects of the life of the Kurds, including history, literature, poetry, and folklore in most of its details of proverbs, tales, stories, songs of joys and sorrows, and love, according to the regions and cities he visited, without Kurdish dialects and did not change anything from them, to be a dictionary of the Kurdish language in the future, because it is heading towards loss. He said and authored many books and articles on this aspect, where he devoted his life to this work to preserve this heritage. The importance of this study comes in shedding light on the life and stages of a venerable education. This study also deals with his intellectual upbringing, the factors that affected him, and his efforts and activity in the service of kurdology. The focus was on the scientific efforts that he made after his asylum in Austria in 1992, including the establishment of the Kurdish Institute “Vin” and the Jasmi Jalil Library, the disclosure of issues 10-12 of the Kurdistan Newspaper, and the collection of Kurdish manuscripts that he obtained in different countries, which amounted to 250 Kurdish manuscripts.